Rice Sufficiency Projections in Malang Regency Towards Golden Indonesia 2045 - Hanna Innayah Rochmawati; Zainul Arifin; Titis Surya Maha Rianti (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
For most Indonesians, rice is a staple of their diet. Food supply, particularly from domestic rice production, is correlated with food availability. Stable rice production is one of the determining factors in achieving food self-sufficiency towards the golden Indonesia 2045 and making Indonesia the world's food barn. This investigation aims to assess the adequacy of rice availability in Malang Regency in support of Golden Indonesia 2045. The data sources used were rice production and rice consumption data for 2010–2023, obtained from the Central Statistics Agency of Malang Regency and the Food Security Service of Malang Regency. The analysis methodology used is an ARIMA-Box-Jenkins analysis to project rice production and consumption. The analysis shows that projections of rice production and consumption in Malang Regency have increased each year. The highest rice production projection is in 2045, at 390,655 tons. The average growth of rice production is 1.06%. The highest rice consumption projection is in 2045, at 277,577 tons, with an average annual growth rate of 0.8%. Rice production is higher than rice consumption. Thus, overall, Malang Regency is estimated to produce a rice surplus from 2024 to 2045, averaging 92,812 tons.